Jasmonate and salicylic sprays improve cherry tomato fruit productivity and quality in unheated greenhouses - Essa, Bassim Almass; Alwan, Othman Khalid (Agronomía Mesoamericana, 2024)
Introduction. Arable regions often lack sufficient soil nutrients, which means that fertilizers must be used. However, using fertilizers excessively can harm the environment, human health and food safety. Natural growth regulators derived from plants are environmentally friendly and reasonably priced. The phytohormones methyl jasmonate (MeJA) and salicylic acid (SA) are crucial for enhancing plant biomass, quality, productivity and resistance to environmental stresses. Objective. To evaluate the foliar effect of MeJA and SA on fruit quality and production of colorful tomato cultivars under greenhouse conditions. Materials and methods. The trial was conducted at the University of Diyala, Iraq, from December 1, 2022, to June 5, 2023. Foliar applications of 0 mg/L, 200 mg/L SA and 200 mg/L MeJA were evaluated to determine their effects on fruit quality and production of colorful indeterminate cherry tomato cultivars: LA4013, LA353, LA2921, LA3899 and IQ2. A randomized complete block design was used, with each treatment having three replicates. Results. The cultivar IQ2 produced the heaviest fruit (82.13 g), the highest plant yield (4.56 kg/plant), the highest total yield (4.56 t/house) and the highest titratable acidity (0.62 %). The cultivar LA4013 had the highest fruit number (612.88 fruits/plant) and the highest total soluble solids (2.933 %). The foliar application of 200 mg/L SA resulted in the highest chlorophyll index (36.68 SPAD), the highest fruit number (373.73 fruits/plant), the highest plant yield (3.15 kg/plant) and the highest total yield (3.93 t/house). Conclusion. Considering all variables together, the best-performing genotypes were IQ2 and LA4013, which were superior to other genotypes in quality and yield trials. The foliar application of 200 mg/L SA improved both yield and quality of cherry tomatoes under greenhouse conditions.